Dampak Fluktuasi Harga Jagung Terhadap Kesejahteraan Petani Jagung - Rizki Gemala Busyra (Jurnal MeA (Media Agribisnis), 2020)
Price fluctuation is a common phenomenon that occurs in agricultural products, including corn commodities. The price fluctuation of corn commodity will affect the corn farming condition. If the price of corn falls, the income of corn farmers will also decrease. However, if the price of maize increases, the income of corn farmers will also increase. This study aimed to determine the impact of maize price fluctuations on the welfare of maize farmers in Jambi City. This study used the income and costs analysis method and builds econometric equations for income. This income is an indicator to measure the welfare of farmers. The results showed that the factors affecting the income of maize farmers were seed prices, corn production, maize prices, fertilizer prices and medicine prices. Corn price fluctuations would have an impact on the welfare of corn farmers. Because the statistical value of the price of maize had a significant effect on the income of corn farmers as an indicator of the welfare of corn farmers. If the price of corn rises, the welfare of corn farmers will also increase or vice versa.